Revegetation research 1976 progress report Sub-Projects VE 7.2, 7.3, and 7.4 - Vaartnou & Sons Enterprises Ltd. (1977)
Laboratory studies were conducted during 1976 to investigate native grasses and legumes potentially useful for revegetation on various soils. Plant growth was tested in various soils with and without the addition of fertilizer in the greenhouse and ill growth chambers. The Genera tested were: Agropyron Alopecurus, Bromus, Calamagrostis, Festuca, Phalaris, Phleum, Poa, Puccinellia, Astragalus, Hedysarum, Lupinus, Oxytropis, Glycyrrhiza, Lathyrus, Thermopsis, and Vicia. Field studies were conducted at Woodbend Station, Devon. Germination and early establishment were observed on unscarifled, fall-planted and scarified, spring-planted legumes. Work was begun at the Alberta Environment Research Station at Vegreville. Native grasses, naturalized grasses, agricultural varieties of grasses, and native and agricultural varieties of legumes were planted to be evaluated in the uniformity garden. Ft Fort McMurray, research areas were partly established on the Great Canadian Oil Sands Ltd. tailings dike site and the AOSERP Mildred Lake facility. The development of the seed production test sites at Peers, Waskatenau, and High Level were continued. Native species of legumes were seeded at the Peers legume seed-increase nursery. Native grass seed for plants which had been sown the previous year at four different sites in Alberta were harvested. The following tentative conclusions may be used for the planning of Future studies: (i) Plant growth can be established on tailings sand if there is adequate moisture present, but time of planting seems to be a critical factor in establishment; (ii) Native legumes can produce root nodules without the add1tion of inoculum, but capacity to produce nodules on tailings sand varies among species; (iii) Nutrient requirements and soil preferences of native species vary widely. However, it is difficult to establish plant growth on soils with a low pH, a high conductivity (i.e. high salt concentration), or, a high aluminum level; (iv) A high level of available fertilizer may wholly or partially ...